East Atlantic Pattern Drives Multidecadal Atlantic Meridional Overturning Circulation Variability During the Last Glacial Maximum - Song, Zhaoyang; Latif, Mojib; Park, Wonsun (FID GEO, 2019)
The variability of the Atlantic meridional overturning circulation (AMOC) and its governing processes during the Last Glacial Maximum (LGM) is investigated in the Kiel Climate Model. Under LGM conditions, multidecadal AMOC variability is mainly forced by the surface heat flux variability linked to the East Atlantic pattern (EAP). In contrast, the multidecadal AMOC variability under preindustrial conditions is mainly driven by the surface heat flux variability associated with the North Atlantic Oscillation. Stand-alone atmosphere model experiments show that relative to preindustrial conditions, the change in AMOC forcing under LGM conditions is tightly linked to the differences in topography.